Gender and integrated area development projects: lessons from Cato Manor, Durban - Todes, Alison; Beall, Jo (Cities, 2004)
The paper examines whether integrated area development projects are particularly well placed to recognize the complexity and diversity of gender relations and provide important space for gender sensitive planning and practice. It recounts the case of the Cato Manor project in Durban, South Africa where, despite no explicit focus on gender in design, practices were remarkably consistent with the prescriptions of the urban gender planning literature. It is argued that a multi-sectoral and integrated approach offers space for innovation and close attention to local dynamics. Hence despite a disjuncture between planning and implementation, a nuanced gender aware approach emerged. There were also limitations and these are highlighted, recognizing feminist critiques of area-based development that show gender-aware practice is not automatic. In the case of Cato Manor, it depended on facilitative political and policy conditions, politically empowered and organized women and gender-aware professionals. Nevertheless, the area-based focus of the project was also helpful.
Keywords: Integrated area development, gender, South Africa.